Creative Writing at the English Department of WWU Münster - Meinig, Sigrun (Satura, 2018)
This short introduction to the Creative Writing Section in the inaugural edition of Satura, to which this group is very happy to be able to contribute, is meant to provide a short background on our work and on how this section came about.